Incidence of Osteomyelitis in Sacral Decubitus Ulcers and Recommendations for Management. Issue 6 (June 2020) - Crespo, Alexander; Stevens, Nicole M.; Chiu, Ernest; Pham, Vinh; Leucht, Philipp
Abstract : Stage-4 pressure ulcers are defined as ulcerations that violate the fascia and expose underlying bone, muscle, and tendon. Exposed bone is always colonized by bacteria, but this does not necessarily lead to osteomyelitis. The rates of osteomyelitis in exposed bone in stage-4 pressure ulcers range from 14% to 86%. There has been no evidence that the presence of osteomyelitis leads to higher complication rates following flap coverage. There has been no evidence that bone biopsy and preoperative treatment of osteomyelitis have any benefit before flap coverage.